Diagnostic Tools for Governance in Fragile States : Lessons, Trends and Suggestions - Hyden, Goran; Agborsangaya -Fiteu, Ozong (World Bank, Washington, DC, 2017)
The purpose of this issues note is to review the experience in and outside the World Bank of using different diagnostic tools in fragile state situations. It will identify trends in the use of such tools, lessons learnt, and arrive at suggestions for the future. Because governance has continued to be a major concern in the international community, over the years this has led to a growing diversity in the application of the concept. With this diversification the types of assessment in use have also increased, a process that reflects two things. First, each agency tends to design an assessment to meet its own program needs. Second, diagnostic tools have often fallen short of expectations leading agencies to develop new ones, including more recently political economy studies that go beyond what was at least until recently mainstream types of assessing governance. Accepting the diversity of definitions and assessments, this note does not intend to review the whole field. A diagnostic tool here refers to the approach and methodology used in assessing governance. Choice of tool has a direct bearing on how an activity is designed and carried out. Making the right choice, therefore, is important. A tool may become 'main stream' and the original rationale for its use disappears. It is applied because everyone else is using it or there is pressure to use the same tool as others. A shift to other tools, however, may become necessary because existing tools do not deliver. Such a shift is occurring in the governance field where a focus on institutions is being increasingly complemented, if not replaced, by a studies of underlying political economy factors. This Note tries to trace this process by highlighting both specific and more general experiences with tools used to assess governance. Fragile states or situations are not typical but they give rise to governance challenges that more than other contexts test the limits of particular tools. This becomes an especially important issue given that what works in countries that are not fragile seems to fall short of the same achievement in fragile situations.